What can Indonesian Businesses Learn from the We Mean Business Initiative to Address Climate Change? - Mychelisda, Erla; Firdaus, Nur (UI Scholars Hub, 2021)
Climate change has been a much-discussed topic around the globe, and all stakeholders, including the business sector, must take collective and serious actions. The We Mean Business (WMB) initiative is a non-profit organisation that supports companies to develop policies and accelerate the transition to a low-carbon economy and achieve sustainable business. On the other hand, Indonesia, as one of the world biggest emitters and signed the Paris Agreement, are also required to meet its climate pledge. Unfortunately, not many Indonesian businesses have shown their contribution to climate change. This study aims to analyse the companies’ commitments under the WMB coalition and evaluates the progress, risks, and opportunities they have faced when fulfilling these task. Concerning the existing condition of the Indonesian business sector, this study is expected to provide lessons learnt from companies around the world joining the WMB coalition. For analysis, a qualitative method through desk research was employed in which any documents related to the report of companies’ commitment to climate change were thoroughly interpreted. Thirty-eight companies joining the WMB from eleven sectors were selected as the sample. The results show that the science-based target initiative (SBTi) is the most popular, while sustainable fuels are a less preferable commitment among the firms. Besides, most companies have shown considerable progress in achieving their duty towards climate change. These results can be lessons learnt for Indonesian businesses to implement the same initiatives to contribute to emissions reductions so that Indonesia can meet its climate pledge within the specified time.